Medication use for the management of professional performance : between invisibility and social normalisation - Lopes, Noémia; Tavares, David; Pegado, Elsa; Raposo, Hélder; Rodrigues, Carla (Taylor & Francis, 2024)
This article aims to explore pharmaceuticalisation processes in professional work contexts. The approach focuses on identifying patterns of medicine and dietary supplement use for managing work performance, and on discussing the relationship between these consumption practices and work-related pressure factors. This analysis adapts the notions of ‘normalisation’ to understand the extent of cultural acceptability of these practices, and the notion of ‘differentiated normalisation’ to capture the tension between the trend towards normalisation of such consumption and its partial social (in)visibility within work settings. Empirical support for this analysis is based on a sociological study conducted in Portugal on professions under high performance pressures. The study involved three professional groups – nurses, journalists and police officers. A mixed methods approach was used, including focus groups, questionnaires and semi-structured interviews. Overall, the results show a trend towards the use of medicines and supplements for performance management, which reveals itself as a cultural response to work-related social pressures. Such consumption coexists with irregular patterns of either occasional or long-term use, as well as heterogeneous processes of ‘normalisation’ and ‘hidden’ consumption. Conclusions point to a social interconnection between the intensification of work pressures and the pharmaceuticalisation of work performance.
Keywords: Medication; pharmaceuticalisation; performance consumptions; work contexts; professional pressure; differentiated normalisation